Answer:
25/14
Step-by-step explanation:
Answer:
= 3n + 4
Step-by-step explanation:
there is a common difference between consecutive terms , that is
10 - 7 = 13 - 10 = 16 - 13 = 3
this indicates the sequence is arithmetic with nth term
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
here a₁ = 7 and d = 3 , then
= 7 + 3(n - 1) = 7 + 3n - 3 = 3n + 4
In this equation, you are solving for y. Simply isolate the variable by adding 1/4 to each side. The -1/4 and 1/4 will cancel out on the right side of the equation, leaving only y:
5/4 = y - 1/4
5/4 + 1/4 = y - 1/4 + 1/4
6/4 = y
y = 6/4
Don't forget to simplify y:
y = 3/2
Answer:
x = - 4, x = 2
Step-by-step explanation:
Given
3x² + 6x - 24 = 0 ( divide through by 3 )
x² + 2x - 8 = 0 ← in standard form
(x + 4)(x - 2) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 4 = 0 ⇒ x = - 4
x - 2 = 0 ⇒ x = 2